Extreme values of Young's modulus and Poisson's ratio of hexagonal crystals. (July 2019) - Gorodtsov, Valentin A.; Lisovenko, Dmitry S.
Highlights: The variability of Youngs modulus and Poissons ratio for hexagonal crystals was studied. The expressions for the extreme values of Youngs modulus and Poissons ratio are obtained. Classification schemes for extreme values of Young's modulus and Poisson's ratio are proposed. Abstract: The variability of Young's modulus and Poisson's ratio for hexagonal crystals was studied. Expressions for three stationary values of Young's modulus and eight stationary values of Poisson's ratio were obtained. Numerical analysis of the extrema of the elastic characteristics for crystals was given based on experimental data from the Landolt-Börnstein reference book. Classification schemes for extreme values of Young's modulus and Poisson's ratio are proposed. Data on hexagonal materials with negative Poissons ratio are obtained. It was shown that global extremes of Poisson's ratio can exceed the value 0.5, which is the upper limit for isotropic materials. On the other hand, hexagonal crystals were not found for which the global minimum value was less than − 1 (lower limit for isotropic materials).